Economic evaluation of nivolumab combined with ipilimumab in the first-line treatment of advanced melanoma in Japan. (1st December 2020) - Paly, Victoria Federico; Hikichi, Yusuke; Baker, Timothy; Itakura, Eijun; Chandran, Nisha; Harrison, James
Abstract: Aims: The objective of this study was to evaluate the cost-effectiveness of nivolumab in combination with ipilimumab (nivo + ipi) compared to current therapeutic alternatives in first-line treatment of patients with advanced melanoma from the Japanese national healthcare payer perspective using 48-month survival data from the CheckMate 067 Phase III trial. Materials and methods: A three-state partitioned survival model was developed from projections of overall survival (OS) and progression-free survival (PFS) to estimate accrued quality-adjusted survival and costs over a 30-year time horizon. The analysis included nivo + ipi, nivolumab, and ipilimumab monotherapies (the three treatments included in CheckMate 067). Drug acquisition, administration, disease management, subsequent therapy, and adverse event (AE) costs were obtained via published sources and expert input (solicited via Delphi panel). AE frequencies were collected from the Checkmate 067 trial. Utility weights were estimated from the Checkmate 067 trial, based on Japanese tariffs. Results were presented as incremental cost-utility ratios (ICURs, cost per quality-adjusted life-year (QALY)). Results: Nivo + ipi had the greatest estimated survival among the three competing treatments, followed by nivolumab monotherapy accruing the second greatest survival. The incremental cost-effectiveness of nivo + ipi was ¥778, 000 per QALY vs. nivolumab and ¥1, 584, 000 per QALY vs. ipilimumab. The results indicate that nivo + ipi is cost-effective in Japan when compared to a threshold of ¥7, 500, 000 per QALY. This finding was found to be generally robust to sensitivity and scenario analyses. Limitations: Limitations include uncertainty in long-term survival extrapolations and lack of Japan-specific clinical data. Conclusions: This analysis indicates that adding ipilimumab to nivolumab therapy represents a cost-effective new treatment option for patients with unresectable malignant melanoma in Japan.